Step * 1 2 of Lemma integral-rsum


1. : ℤ
2. 0 < d
3. ∀[n:ℤ]. ∀[a,b:ℝ]. ∀[f:{f:{n..(n (d 1)) 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ
                          ∀i:{n..(n (d 1)) 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} ].
     (a_∫-b Σ{f[i;x] n≤i≤(d 1)} dx = Σ{a_∫-f[i;x] dx n≤i≤(d 1)})
4. : ℤ
5. : ℝ
6. : ℝ
7. {f:{n..(n d) 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ
        ∀i:{n..(n d) 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} 
⊢ a_∫-b Σ{f[i;x] n≤i≤d} dx = Σ{a_∫-f[i;x] dx n≤i≤d}
BY
(RWO "rsum-split-last" 0
   THEN (Auto THEN Try ((BLemma `radd_functionality` THEN Auto)))
   THEN Try ((BLemma `rsum_functionality` THEN Auto THEN THEN Auto THEN DVar `f' THEN Unhide THEN Auto))) }

1
1. : ℤ
2. 0 < d
3. ∀[n:ℤ]. ∀[a,b:ℝ]. ∀[f:{f:{n..(n (d 1)) 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ
                          ∀i:{n..(n (d 1)) 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} ].
     (a_∫-b Σ{f[i;x] n≤i≤(d 1)} dx = Σ{a_∫-f[i;x] dx n≤i≤(d 1)})
4. : ℤ
5. : ℝ
6. : ℝ
7. {f:{n..(n d) 1-} ⟶ [rmin(a;b), rmax(a;b)] ⟶ℝ
        ∀i:{n..(n d) 1-}. ifun(λx.f[i;x];[rmin(a;b), rmax(a;b)])} 
⊢ a_∫-b Σ{f[i;x] n≤i≤(n d) 1} f[n d;x] dx {a_∫-f[i;x] dx n≤i≤(n d) 1} a_∫-f[n d;x] dx)


Latex:


Latex:

1.  d  :  \mBbbZ{}
2.  0  <  d
3.  \mforall{}[n:\mBbbZ{}].  \mforall{}[a,b:\mBbbR{}].  \mforall{}[f:\{f:\{n..(n  +  (d  -  1))  +  1\msupminus{}\}  {}\mrightarrow{}  [rmin(a;b),  rmax(a;b)]  {}\mrightarrow{}\mBbbR{}| 
                                                    \mforall{}i:\{n..(n  +  (d  -  1))  +  1\msupminus{}\}.  ifun(\mlambda{}x.f[i;x];[rmin(a;b),  rmax(a;b)])\}  ].
          (a\_\mint{}\msupminus{}b  \mSigma{}\{f[i;x]  |  n\mleq{}i\mleq{}n  +  (d  -  1)\}  dx  =  \mSigma{}\{a\_\mint{}\msupminus{}b  f[i;x]  dx  |  n\mleq{}i\mleq{}n  +  (d  -  1)\})
4.  n  :  \mBbbZ{}
5.  a  :  \mBbbR{}
6.  b  :  \mBbbR{}
7.  f  :  \{f:\{n..(n  +  d)  +  1\msupminus{}\}  {}\mrightarrow{}  [rmin(a;b),  rmax(a;b)]  {}\mrightarrow{}\mBbbR{}| 
                \mforall{}i:\{n..(n  +  d)  +  1\msupminus{}\}.  ifun(\mlambda{}x.f[i;x];[rmin(a;b),  rmax(a;b)])\} 
\mvdash{}  a\_\mint{}\msupminus{}b  \mSigma{}\{f[i;x]  |  n\mleq{}i\mleq{}n  +  d\}  dx  =  \mSigma{}\{a\_\mint{}\msupminus{}b  f[i;x]  dx  |  n\mleq{}i\mleq{}n  +  d\}


By


Latex:
(RWO  "rsum-split-last"  0
  THEN  (Auto  THEN  Try  ((BLemma  `radd\_functionality`  THEN  Auto)))
  THEN  Try  ((BLemma  `rsum\_functionality`
                        THEN  Auto
                        THEN  D  0
                        THEN  Auto
                        THEN  DVar  `f'
                        THEN  Unhide
                        THEN  Auto)))




Home Index